Vacciner contre la COVID-19 ? Interroger l’agenda hégémonique de la santé globale depuis la Guinée - Sylla, Gassim; Le Marcis, Frédéric (Anthropologica, 2024)
Guinea has a low COVID-19 vaccination coverage (28% as of 22 February 2023). Instead of seeing this low vaccination rate as a failure, we suggest discussing this as a local response to the global health agenda. This study is built on the ethnography of Guinea’s vaccination implementation and was conducted by the authors from March 2020 to October 2020 in the capital and the country’s interior. Healthcare stakeholders and individuals, both vaccinated and unvaccinated, were surveyed, and the political context under which the campaign was rolled out was analyzed. Far from being a homogeneous commentary by global healthcare stakeholders, we describe how the vaccination policy is dependent on multilateral and bilateral relations that shape its vaccination availability. Procuring input, the health situation and political tension associated with COVID-19 call into question the legitimacy of preventive measures, specifically vaccination. On the other hand, promised actions in the global health arena to respond to the COVID-19 epidemic (lockdown, vaccination) disregarded the political and biological conditions encountered by the virus in Guinea. By mobilizing the concept of situated biology (lock), the relevance of a universal agenda for global health must be discussed.